Interaction Between Agricultural Environmental Exposure and Inflammatory Biomarkers in Breast Cancer Risk - Abdussalam, Arrizqi Hafidh; Kurniati, Yuni Prastyo; Romadhon, Yusuf Alam; Permatasari, Happy Kurnia; Sutrisna, Em (Medical Laboratory Technology Journal, 2025)
Breast cancer remains the most common malignancy among women worldwide, and environmental exposures may contribute to breast carcinogenesis through inflammatory pathways such as NLR, PLR, and interferon-γ. This study aimed to examine the association between agricultural environmental exposure, represented by rice field area, and inflammatory biomarkers including the Neutrophil-to-Lymphocyte Ratio, Platelet-to-Lymphocyte Ratio, and Interferon-γ in breast cancer. A case–control method was applied to 128 histopathologically confirmed samples consisting of 100 malignant (Invasive Carcinoma NST) and 28 benign (Fibroadenoma Mammae) breast tumors; hematologic indices were derived from preoperative blood tests, IFN-γ expression was analyzed immunohistochemically, and rice field proportions near participants’ residences were obtained from national statistics, with data analyzed using Chi-square and multivariate logistic regression. The results showed that agricultural exposure (rice field ≥60%) was not significantly associated with breast cancer (p = 0.703), whereas elevated NLR (OR = 4.89, p = 0.014), PLR (OR = 12.13, p = 0.017), and IFN-γ expression ≥20% (aOR = 23.94, p = 0.049) were significantly associated with malignancy. In conclusion, although agricultural land area was not a direct risk factor, inflammatory and immune biomarkers—particularly IFN-γ—served as strong predictors of breast cancer, indicating their potential utility in risk stratification for agrarian populations.